About some autumn weed vegetation in small size arable fields of Veneto: their framing and remarks on summer crop weed associations of Northern Italy - Tasinazzo, Stefano (Hacquetia, 2023)
A late summer-autumn research was conducted in Veneto region (NE-Italy) inside kitchen gardens and patato fields of outer pre-Alps, and in asparagus growing in low Po plain nearby the Adriatic coast. Original vegetation-plot records were compared with outdated and recent materials from Italy, especially N-Italy, and with comparable associations from Central and South-Eastern Europe, to ensure a consistent syntaxonomical frame of this highly dynamic vegetation. At the same time it was possible to clarify the actual occurrence of past coenosis, quoted by Italian authors for the Po plain. The analysis resulted in confirming and extending the occurrence of Echinochloo-Setarietum pumilae in north-eastern Italian territories, and also in confirming the persistence of Panico-Polygonetum persicariae. The recognised historical presence of Veronico-Lamietum hybridi occurring in pre-Alps and Dolomites needs confirmation. Further regional-scale investigations inside summer crop weed vegetation appear necessary.